DETERMINANTS OF GOVERNMENT FINANCIAL REPORT QUALITY IN HEALTH QUARANTINE TECHNICAL IMPLEMENTING UNITS OF THE MINISTRY OF HEALTH - Muhammad Khairy Muflih; Syaiful Hifni; Sarwani (JAT : Journal Of Accounting and Tax, 2026)
This study aims to examine the effects of human resource competence, government accounting standards, government internal control systems, and information technology utilization on the quality of financial reports in Health Quarantine Technical Implementing Units (UPTs) within the Ministry of Health. This study employed a quantitative approach using a survey method and a census sampling technique involving all financial management personnel across 51 Health Quarantine Technical Implementing Units, with data analyzed using multiple linear regression. The findings indicate that human resource competence, government accounting standards, and government internal control systems each have a positive and significant effect on the quality of financial reports. In contrast, information technology utilization has no significant effect and exhibits a negative direction, indicating the presence of a technology paradox resulting from a financial system that has not yet been fully integrated. Simultaneously, the four variables collectively have a significant effect on the quality of financial reports in Health Quarantine Technical Implementing Units within the Ministry of Health.